Simulating current and future water resources development in the Blue Nile River Basin. - McCartney, Matthew P.; Alemayehu, T.; Easton, Z.M.; Awulachew, Seleshi Bekele (Routledge, 2012)
Agricultural water management (AWM) interventions in the Nile Basin are a key to improve agricultural production and productivity. AWM interventions can be categorized based on spatial scales, sources of water and type of technologies for water management in control, lifting, conveyance and application. Various combinations of these interventions are available in the Nile Basin. Successful application of AWM interventions should consider the full continuum of technologies in water control, conveyance and field applications. AWM technology intervention combined with soil fertility and seed improvement may increase productivity up to threefold. Similarly, data sets used from a representative sample of 1517 households in Ethiopia shows that the average treatment effect of using AWM technologies is significant and has led to an income increase of US$82 per household per year, on average. The findings indicated that there are significantly low poverty levels among users compared to non-users of AWM technologies, with about 22 per cent less poverty incidence among users compared to non-users of ex situ AWM technologies. The Nile basin has 10 major water control structures that are used for various purposes including irrigation, hydropower, flood and drought control, and navigation. The Water Evaluation And Planning (WEAP) model is applied to the Nile Basin, considering existing infrastructure, and scenarios of water use under current, medium term and Iong term. The major water use interventions that affect water availability in rivers are related to irrigation development. Accordingly, the irrigation areas of the current, medium-term and long-term scenarios in the Nile Basin are, respectively, about 5.5,8 and 11 million ha, with water demands of 65,982 million m 94,541 million m' and 127,661 million m respectively. The total irrigation water demand for the current scenario is lower than the Nile basin annual flow. The total irrigation water demand for the medium-term scenario exceeds the Nile mean annual flow marginally. The irrigation demands for the long-term scenario are considerably greater than the mean annual flow of the Nile basin, assuming the existing management practice and irrigation water requirement estimation of the countries. The river water would therefore will not satisfy irrigation water demands in the long term unless the irrigation efficiency is improved, water saving measures are implemented and other sources of water and economic options are explored.